Profilaksis Ekstrak Brokoli terhadap Kadar Gula Darah pada Tikus putih yang Diinduksi Deksametason - PUTU AMANDA SILCIE F.S.U; FITRI HANDAJANI; MOH. FATHI ILMAWAN; PRASETYADI, FRANSISCUS O. H. (Hang Tuah Medical Journal, 2024)
Diabetes mellitus is a chronic metabolic disease with chronic hyperglycemia. The increasing consumption of dexamethasone, especially during the COVID-19 pandemic, results in an increase in patients with hyperglycemia and even increases the risk of developing type 2 diabetes mellitus (T2DM). Glucocorticoids, including dexamethasone, often cause drug-induced hyperglycemia and drug-induced diabetes. Prophylactic therapy with natural ingredients, such as broccoli, which contains antidiabetic, antihyperglycemic, antioxidant and anti-inflammatory agents from its flavonoid compounds is needed to prevent or reduce hyperglycemia and the risk of T2DM. This study aims to determine the effect of prophylactic administration of broccoli extract (Brassica oleracea var. italica) as an inhibition against the increase in fasting blood glucose levels in rats caused by dexamethasone induction. 24 Wistar male white rats (Rattus norvegicus) were divided into 3 different groups; K(-) = no treatment, K(+) = subcutaneous dexamethasone induction 10 mg/KgBB/day for 10 days, KP = prophylaxis of broccoli extract 1000 mg/KgBB/day for 7 days and broccoli extract was continued along with subcutaneous dexamethasone induction 10 mg/KgBB/day for 10 days. The study lasted for 24 days and on the 25th day blood samples were taken for fasting blood glucose measurement. The mean fasting blood glucose of K(-) = 173.62; K(+) = 304.89; KP = 180.50. One Way Anova parametric test results obtained significance p = 0.001 (p < 0.05). Post Hoc LSD results; K(+) and KP have a significance of p = 0.001 (p < 0.05). Prophylactic administration of broccoli extract 1000 mg/KgBB can inhibit the increase (decrease) fasting blood glucose levels of Wistar male white rats induced by dexamethasone 10 mg/KgBB/day for 10 days.